AGING STRONG 2020: PROMOTING RESILIENCE, PURPOSE, OPTIMISM, AND SOCIAL CONNECTEDNESS AMONG OLDER ADULTS. (11th November 2018) - McGinn, M; Tkatch, R; Kraemer, S; Wu, L; Martin, D; Wicker, E
Abstract: Health is often defined in clinical terms yet many older adults self-report aging successfully regardless of clinical health status. Therefore, it is important to consider a population health perspective for older adults to develop effective interventions. The purpose of this study was to investigate the physical and psycho-social well-being of AARP Medicare Supplement insureds by objective health status and measure its impact on quality of life. Participants were stratified by Hierarchical Condition Category (HCC) scores (healthy<.50, at risk.51–2.80, and very ill 2.81<). A total of 4, 664 participants completed a mailed survey. Physical and mental health, resilience, social support, purpose in life, and health literacy decreased with HCC category, providing evidence for intervention opportunities. In separate regression models, social support and purpose in life predicted quality of life demonstrating its importance for older adults. Overall, these data provide strong support to develop interventions that focus on promoting Aging Strong 2020.